Beyond work ethic: Religion, individual and political preference - Christoph Carl Basten; Frank Betz (ETH Zurich, KOF Swiss Economic Institute, 2012)
We investigate the effect of Reformed Protestantism, relative to Catholicism, on preferences for leisure, and for redistribution and intervention in the economy. We use a Fuzzy Spatial Regression Discontinuity Design to exploit a historical quasi-experiment in Western Switzerland, where in the 16th century a hitherto homogeneous region was split and one part assigned to adopt Protestantism. We find that Reformed Protestantism reduces referenda voting for more leisure by 12, for redistribution by 7, and for government intervention by 6 percentage points. These preferences translate into higher per capita income as well as greater income inequality.
Keywords: 330; Protestantismus; Katholizismus; Regionale Einkommensverteilung; Leistungsmotivation; Freizeitverhalten; Arbeitsethik; Geschichte; Schweiz (West); Test